Morinda officinalis oligosaccharides improves sperm motility via the gut microbiota and the IGF-1/PI3K/mTOR signaling pathway - Hu, Jiajia; Li, Guoxuan; Ouyang, Bingxue; Wang, Anguo; Li, Yejuan; Lu, Hui (Frontiers in Endocrinology, 2026)
BackgroundThis study aimed to evaluate the efficacy of Morinda officinalis oligosaccharides (MOS) in improving sperm motility and quality in a gossypol-induced asthenozoospermia mouse model, and to explore the potential underlying mechanisms.MethodsMale C57BL/6J mice were randomly assigned to six groups: normal control, model, low-dose MOS (12.5 mg/kg), medium-dose MOS (25 mg/kg), high-dose MOS (50 mg/kg), and positive control (L-carnitine 10 mg/kg). Asthenozoospermia was induced by gossypol (20 mg/kg) injection every 3 days for 30 days, followed by MOS gavage for 14 days. Sperm motility, hormone levels, and histopathological changes were analyzed, and gut microbiota composition was analyzed using 16S rRNA sequencing. Mechanistic validation was performed using Anaerococcus transplantation and rapamycin co-treatment with MOS.ResultsGossypol impaired sperm concentration and motility and induced luminal sperm depletion with vacuolation in the epididymis, without overt structural lesions in the testes, liver, or kidneys. MOS improved sperm motility in a dose-dependent manner, restored testosterone, normalized white blood cells and blood urea nitrogen levels, and reduced sperm morphological abnormalities. High-dose MOS significantly increased microbial α-diversity and enriched Anaerococcus, shifted the microbial community structure toward that of the normal group. MOS and Anaerococcus transplantation activated the IGF-1/PI3K/mTOR pathway, increased Bcl-2, and reduced Cleaved Caspase-3 expression, whereas rapamycin attenuated these improvements, indicating pathway dependence.ConclusionsMOS ameliorates gossypol-induced asthenozoospermia by remodeling the gut microbiota and activating IGF-1/PI3K/mTOR signaling, thereby improving sperm motility and reducing apoptosis. These findings highlight MOS as a promising microbiota-modulating therapeutic strategy for male reproductive dysfunction.